An improved four‐layer capacitor voltage control strategy combined with arm current control for transformerless modular multilevel converters. Issue 5 (2nd December 2022) - Liu, Dan; Xiong, Ping; Xiao, Fan; Lai, Jinmu; Ji, Xiaotong; Wang, Wei
Abstract: In order to improve the performance of the transformerless modular multilevel converters (MMC) under AC and DC grid fault conditions, this paper proposes an improved four‐layer capacitor voltage control strategy combined with arm current control. The proposed control strategy consists of overall submodule capacitor voltage averaging control, leg‐balancing control with flexible weight factor W, arm‐balancing control with zero‐sequence suppression, and inner‐arm individual balancing control. The new concept of weight factor W for leg‐balancing control is also originated, considering negative‐sequence current and DC circulating current jointly from power point of view. The proposed approach effectively realizes the capacitor voltage balance, ac‐side current tracking, and unwanted circulating current elimination. The practical implementation of the proposed control strategy and the experimental results from a downscale three‐phase transformerless MMC prototype are presented to validate the performance of the proposed four‐layer capacitor voltage control strategy under grid faults. Abstract : This paper proposes an improved four‐layer capacitor voltage control strategy combined with arm current control for Transformerless MMC. We originate the new concept of weight factor W for leg‐balancing control, considering negative‐sequence current and dc circulating current jointly from power point of view. The proposed approach effectively realizes the capacitor voltage balance, ac‐side current tracking, and unwanted circulating current elimination.